Reflections on practices of U laya nwana : towards an Afro-sensed approach - Mudau, Ndidzulafhi; Matshidze, Pfarelo; Netshandama, Vhonani; Masoga, Alpheus (African renaissance, 2018)
Traditional African practices of u laya nwana are currently influenced by dominant contemporary practices which are largely Euro-western in nature. U laya nwana seems problematic in families these days. There seems to be a contradiction between how parents wish to raise their children and what the actual parenting practices are. Most parents, despite their intention to blend traditional norms and values in u laya nwana are faced with challenges on how to infuse them in modern life. The researcher departs from a premise that, if u laya nwana is infused with traditional norms and values, the practice will be more effective in grooming well-rounded citizens. The article reflected on how ndayo ya nwana could contribute towards the revitalisation of the young children in South Africa. The article site was located within the Vhembe District, in the Limpopo Province of South Africa. This article utilised the qualitative research method of enquiry with the use of in-depth interviews in order to gain insight into the perceptions of the indigenous knowledge holders in the area of u laya nwana. It is anticipated in this article that new insights on the depth and wisdom practised by indigenous people in the philosophy of u laya nwana will be identified. The Afro-sensed learning strategies were developed to revive ndayo-guidance on up-bringing children of South Africa.